Construction of CuCo2O4@NiFe-LDH Core–Shell Heterostructure for High-Performance Hybrid Supercapacitors - Yang Chen; Man Li; Chengyu Xue; Fuxiang Wei (Metals)
Transition metal oxides (TMOs) are considered to be highly promising materials for supercapacitor electrodes due to their low cost, multiple convertible valence states, and excellent electrochemical properties. However, inherent limitations, including restricted specific surface area and low electrical conductivity, have largely restricted their application in supercapacitors. In this paper, core–shell heterostructures of nickel–iron layered double hydroxide (NiFe-LDH) nanosheets uniformly grown on CuCo2O4 nanoneedles were synthesized by hydrothermal and calcination methods. It is found that the novel core–shell structure of CuCo2O4@NiFe-LDH improves the electrical conductivity of the electrode materials and optimizes the charge transport path. Under the synergistic effect of the two components and the core–shell heterostructure, the CuCo2O4@NiFe-LDH electrode achieves an ultra-high specific capacity of 323.4 mAh g−1 at 1 A g−1. And the capacity retention after 10,000 cycles at 10 A g−1 is 90.66%. In addition, the assembled CuCo2O4@NiFe-LDH//RGO asymmetric supercapacitor device achieved a considerable energy density (68.7 Wh kg−1 at 856.3 W kg−1). It also has 89.36% capacity retention after 10,000 cycles at 10 A g−1. These properties indicate the great potential application of CuCo2O4@NiFe-LDH in the field of high-performance supercapacitors.